Balance, Lateropulsion, and Gait Disorders in Subacute Stroke. (27th April 2021) - Dai, Shenhao; Piscicelli, Céline; Clarac, Emmanuelle; Baciu, Monica; Hommel, Marc; Pérennou, Dominic
Abstract : Objective: To test the hypothesis that impaired body orientation with respect to gravity (lateropulsion) would play a key role in poststroke balance and gait disorders. Methods: Cohort study of 220 individuals consecutively admitted to a neurorehabilitation ward after a first hemisphere stroke (DOBRAS cohort [Determinants of Balance Recovery After Stroke] 2012–2018, ClinicalTrials.gov: NCT03203109), with clinical data systematically collected at 1 month, then at discharge. Primary outcomes were balance and gait disorders, quantified by the Postural Assessment Scale for Stroke and the modified Fugl-Meyer Gait Assessment, to be explained by all deficits on day 30, including lateropulsion assessed with the Scale for Contraversive Pushing. Statistics comprised linear regression analysis, univariate and multivariate analyses, and receiver operating characteristic curves. Results: Lateropulsion was frequent, especially after right hemisphere stroke (RHS, D30, 48%; discharge 24%), almost always in right-handers. Among all deficits, impaired body orientation (lateropulsion) had the most detrimental effect on balance and gait. After RHS, balance disorders were proportional to lateropulsion severity, which alone explained almost all balance disorders at initial assessment (90%; 95% confidence interval [CI] [86–94], p < 0.001) and at discharge (92%; 95% CI 89–95, p < 0.001) and also the greatest part of gait disorders at initial assessment (66%; 95% CI 56–77, p < 0.001) and at discharge (68%; 95% CI 57–78, p < 0.001). Conclusion: Lateropulsion is the primary factor altering poststroke balance and gait at the subacute stage and therefore should be systematically assessed. Poststroke balance and gait rehabilitation should incorporate techniques devoted to misorientation with respect to gravity.